Cracking Difficult Biliary Stones - Phonthep Angsuwatcharakon; Rungsun Rerknimitr (Korean Society of Gastrointestinal Endoscopy, 2021)
Apart from difficult biliary cannulation, biliary stone removal is considered one of the hurdles in endoscopic retrograde cholangiopancreatography. Generally, simple common bile duct (CBD) stones can be removed either with an extraction balloon or a basket. However, there are difficult stones that cannot be removed using these standard methods. The most difficult stones are large CBD stones and impacted stones in a tapering CBD. A few decades ago, mechanical lithotripsy was usually required to manage these stones. At present, endoscopic papillary large balloon dilation (EPLBD) of the biliary orifice has become the gold standard for large CBD stones up to 1.5 cm. EPLBD can reduce the procedural time by shortening the stone removal process. It can also save the cost of the devices, especially multiple baskets, used in mechanical lithotripsy. Unfortunately, very large CBD stones, stones impacted in a tapering CBD, and some intrahepatic duct stones still require lithotripsy. Peroral cholangioscopy provides direct visualization of the stone, which helps the endoscopist perform a probe-based lithotripsy either with an electrohydraulic probe or a laser probe. This technique can facilitate the management of difficult CBD stones with a high success rate and save procedural time without significant technical complications.